The Performance Level of the Sudanese Universities in the Light of Quality Standards: An Exploratory Study of the Student's Perspectives in Bakht Al-Ruda and Kordofan Universities in Sudan - Suliman Zakaria Suliman Abdullah (University of Science and Technology, Yemen, 2014)
The Performance Level of the Sudanese Universities in the Light of Quality Standards: An Exploratory Study of the Student's Perspectives in Bakht Al-Ruda and Kordofan Universities in Sudan as a Model            Abstract The Performance Level of the Sudanese Universities in the Light of Quality Standards:An Exploratory Study of the Student's Perspectives in Bakht Al-Ruda and Kordofan Universities in Sudan This paper investigates the student's perspectives at Bakht Al-Ruda and Kordofan Universities in Sudan toward the status quo of University performance in the light of quality standards. The study was conducted during the first and second semesters of the academic year 2012-2013. To achieve this purpose, a questionnaire was developed to collect the data from (860) students. The performance assessment was based on five key areas which describe the status quo of academic performance of higher education institutions in the light of quality standards.  The key areas are: organization and management of academic programs; teaching and learning procedures; resources and educational materials; students support services; and skills development. Based on some descriptive and inferential statistics, the results of the paper show a moderate general trend toward academic performance in the two universities. Resources and educational materials in both universities scored the highest assessment level, in contrast, the lowest assessment is found for the skills development in Bakht Alruda University and for teaching and learning procedures in Kordofan University. Keywords: Performance assessment; University education; Quality assurance, Bakht Al-Ruda University; Kordofan University; Sudan